THE CONTRIBUTION OF PALYNOLOGY IN FIELD DEVELOPMENT - Eko Budi Lelono (Testing Center for Oil and Gas LEMIGAS, 2006)
The reliable interpretation of lateral reservoir distribution is required to gain high accuracy of reserve estimation in the oil field. Apparently, the geometry of reservoirs influences the volume of hydrocarbon. Widespread reservoirs are more preferred than isolated reservoirs because the former tend to store much larger volume of hydrocarbon than the later which usually produce limited volume of hydrocarbon. The lateral reservoir connectivity can be approached using various methods such as well log correlation, seismic correlation, biostratigraphic correlation, etc. In fact, each method sometime provides distinct result compared to that using another method. Therefore, the integration of those methods is actually needed to obtain reliable result. In the studied field, reservoir correlation was firstly constructed base on well log and seismic correlations. It was concluded that each reservoir could be traced along the studied wells. However, in order to cross check this conclusion it is applied palynological correlation as the studied sections are well recognized to represent deltaic sediment which yields rich palynomorph assemblage. It is now believed that palynology will be able to refine the correlation which was reconstructed base on well log and seismic. Data obtained during the analysis is considered to be confidential as this is provided for commercial work which is not public domain. Therefore, detail information of the studied wells cannot be revealed within this paper. The wells are named using numbers such as 1, 2 and 3, whilst reservoirs are labelled in alphabetical order, for example A, B and C. The studied wells were drilled in the oil field, so called Field